1983
DOI: 10.2307/1981643
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Structures: Methods for Exploring Course Content

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.235.251.160 on Sun

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 7 publications
4
38
0
1
Order By: Relevance
“…We are aware of the extent of the simplification when defining concept as such, but for the scope of this article we will adopt a fairly simple interpretation. We concur with Donald (1983) who defines a concept in education theory as "a unit of thought -an element of knowledge […]. According to him, concepts can exist at various levels of generality and abstraction and may be simple or complex" (Donald 1983, p. 32).…”
Section: Concepts In Educationsupporting
confidence: 62%
See 1 more Smart Citation
“…We are aware of the extent of the simplification when defining concept as such, but for the scope of this article we will adopt a fairly simple interpretation. We concur with Donald (1983) who defines a concept in education theory as "a unit of thought -an element of knowledge […]. According to him, concepts can exist at various levels of generality and abstraction and may be simple or complex" (Donald 1983, p. 32).…”
Section: Concepts In Educationsupporting
confidence: 62%
“…According to him, concepts can exist at various levels of generality and abstraction and may be simple or complex" (Donald 1983, p. 32). They can be represented as a separate entity but often exist within a larger framework of related concepts (Donald, 1983;Hulshof & Vroegop, 1990). RNAAS (2003) also formulates concepts as subject matter at the classroom level; for example "sentence structure" and "idiom" (RNAAS, 2003, p. 17).…”
Section: Concepts In Educationmentioning
confidence: 99%
“…In our study of knowledge structures in sixteen university courses across disciplines, we tested a variety of ways of relating course concepts (Donald, 1983). We found that a method of tree structuring worked best with well structured disciplines.…”
Section: Methods Used To Represent Well-structured Knowledgementioning
confidence: 99%
“…These dimensions included (a) the existence of strong paradigms, (b) concern with applications, and (c) concern with life systems. More recently, Donald (1983Donald ( , 1990Donald ( , 1991Donald ( , 1993 has engaged in an ambitious program of research that seeks to understand disciplines with respect to characteristics such as knowledge structure, learningtasks, validation processes, and truth criteria. For example, in one study Donald (1990) interviewed faculty members about the validation processes, truth criteria, and other validation factors characteristic oftheir disciplines.…”
Section: Disciplinary Differences and Their Impact On Reasoningmentioning
confidence: 99%